1995
DOI: 10.2134/jeq1995.00472425002400040028x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Moisture and Soil Texture on the Adsorption of Organic Vapors

Abstract: The fate of volatile organic compounds (VOCs) moving as vapors in the subsurface is dependent on their interaction with the soil. Adsorption of VOC vapors is greatly influenced by soil texture and soil‐water content. The effects of differences in texture and soil‐water content on vapor partition coefficients for trichloroethylene (TCE) were examined. Batch experiments were conducted for a variety of soils and at different soil‐water contents, w, to determine the relationship between the vapor/solid partition c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
71
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 95 publications
(78 citation statements)
references
References 0 publications
7
71
0
Order By: Relevance
“…In contrast to this and despite microbial VOC production, plain soil (without plant roots) is reported to be a VOC sink, strongly dependent on soil temperature and moisture (Asensio et al 2007a). Volatile organic compound sorption to clay minerals (Petersen et al 1995;Chen and Wu 1998;Ruiz et al 1998;Poulsen et al 1998;Serrano and Gallego 2006), solubilisation in the soil aqueous phase (Asensio et al 2007a) or degradation by other microorganisms (Cleveland and Yavitt 1998;Smolander et al 2006;Owen et al 2007;Insam and Seewald 2010) may explain any soil net VOC uptake or variations between replicates (Leff and Fierer 2008). Microbial VOCs may derive from many different metabolic sources, such as primary metabolism like end products of fermentative pathways such as ethanol (ethanol fermentation), butyric acid and acetone (butyric acid fermentation) and as volatile intermediates of aerobic or anaerobic detritus decomposition (Castaldelli et al 2003;Karl et al 2003).…”
Section: Microbial Growth and Voc Productionmentioning
confidence: 90%
“…In contrast to this and despite microbial VOC production, plain soil (without plant roots) is reported to be a VOC sink, strongly dependent on soil temperature and moisture (Asensio et al 2007a). Volatile organic compound sorption to clay minerals (Petersen et al 1995;Chen and Wu 1998;Ruiz et al 1998;Poulsen et al 1998;Serrano and Gallego 2006), solubilisation in the soil aqueous phase (Asensio et al 2007a) or degradation by other microorganisms (Cleveland and Yavitt 1998;Smolander et al 2006;Owen et al 2007;Insam and Seewald 2010) may explain any soil net VOC uptake or variations between replicates (Leff and Fierer 2008). Microbial VOCs may derive from many different metabolic sources, such as primary metabolism like end products of fermentative pathways such as ethanol (ethanol fermentation), butyric acid and acetone (butyric acid fermentation) and as volatile intermediates of aerobic or anaerobic detritus decomposition (Castaldelli et al 2003;Karl et al 2003).…”
Section: Microbial Growth and Voc Productionmentioning
confidence: 90%
“…For organic vapours it has been shown that K sw is highly correlated with soil characteristics such as C content (Petersen et al, 1995), specific surface area or clay content (Yamaguchi et al, 1999), and that K sg is usually significant at soil water contents corresponding to less than five molecular layers of water coverage (Petersen et al, 1995). In this range of soil moisture, direct chemical adsorption onto dry mineral surfaces dominates and can increase the adsorption capacity of soils by several orders of magnitude.…”
Section: Partitioning Of Ocs In the Different Soil Phasesmentioning
confidence: 99%
“…In this range of soil moisture, direct chemical adsorption onto dry mineral surfaces dominates and can increase the adsorption capacity of soils by several orders of magnitude. For these organic vapours the relationship of K sg with soil moisture can be related to soil specific surface area (Petersen et al, 1995) or clay content (Yamaguchi et al, 1999). However these relationships obtained for organic vapours are unlikely to be applicable for OCS because the adsorption mechanisms may be completely different.…”
Section: Partitioning Of Ocs In the Different Soil Phasesmentioning
confidence: 99%
“…Other important interface processes that are intimately linked to soil architecture (matrix and pore systems) and soil OM quality and quantity in combination with organo-clay complexing are sorption of organic vapors (Amali et al, 1994;Petersen et al, 1994Petersen et al, , 1995 as well as dissolved chemicals (de Jonge et al, 2000. Taking a closer look at gaseous phase sorption in soils can lead to a renewed understanding of soil interface phenomena.…”
Section: Sorption (Partitioning) Processes For Organic Chemicalsmentioning
confidence: 99%